2015
DOI: 10.1007/s00382-015-2507-3
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Sea response to climate change in an ensemble of twenty first century scenarios

Abstract: to quantify the socio-economic uncertainty. Our 6-member scenario simulations display a warming and saltening of the Mediterranean. For the 2070-2099 period compared to , the sea surface temperature anomalies range from +1.73 to +2.97 °C and the SSS anomalies spread from +0.48 to +0.89. In most of the cases, we found that the future Mediterranean thermohaline circulation (MTHC) tends to reach a situation similar to the eastern Mediterranean Transient. However, this response is varying depending on the chosen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
248
3
7

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(286 citation statements)
references
References 65 publications
28
248
3
7
Order By: Relevance
“…But in case it is confirmed, it could have important consequences for the future evolution of medicanes, as projections of the Mediterranean mixed layer depth show important future changes, which depend on the emissions scenario (Adloff et al 2015). This would increase the utility of applying ocean-atmosphere coupled RCMs for climate change studies.…”
Section: Discussionmentioning
confidence: 99%
“…But in case it is confirmed, it could have important consequences for the future evolution of medicanes, as projections of the Mediterranean mixed layer depth show important future changes, which depend on the emissions scenario (Adloff et al 2015). This would increase the utility of applying ocean-atmosphere coupled RCMs for climate change studies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Adloff et al (2015) have shown that global warming could modify the circulation patterns. This would induce local differences in sea surface height of up to +10 cm.…”
Section: Spatial Trendsmentioning
confidence: 99%
“…It is composed of LMDz4-regional as atmospheric component (Li et al 2012) and of NEMOMED8 (Beuvier et al 2010;Adloff et al 2015) as oceanic component. NEMOMED8 is a regional configuration of the NEMO ocean model (Madec 2008), setup for the Mediterranean Sea.…”
Section: Lmdz-med-fixed Atlanticmentioning
confidence: 99%
“…In addition, discharges to the sea are rendering the Skhira harbour environment hostile for native species and favouring the proliferation of invasive species (both native and non-native) [30], which represent a possible threat due to climate change [31]. Mosbahi et al (2015) presented a first description of the intertidal macrozoobenthic communities in a small part of the Kneiss Islands.…”
Section: Introductionmentioning
confidence: 99%